2009
DOI: 10.1074/jbc.m109.035147
|View full text |Cite
|
Sign up to set email alerts
|

Control of Promatrilysin (MMP7) Activation and Substrate-specific Activity by Sulfated Glycosaminoglycans

Abstract: Matrix metalloproteinases are maintained in an inactive state by a bond between the thiol of a conserved cysteine in the prodomain and a zinc atom in the catalytic domain. Once this bond is disrupted, MMPs become active proteinases and can act on a variety of extracellular protein substrates. In vivo, matrilysin (MMP7) activates pro-␣-defensins (procryptdins), but in vitro, processing of these peptides is slow, with about 50% conversion in 8 -12 h. Similarly, autolytic activation of promatrilysin in vitro can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
72
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 47 publications
(50 reference statements)
1
72
1
Order By: Relevance
“…We do not know if the heparan sulfates of syndecan bind to MMPs and inhibit their activity directly. It has been shown in some models that MMP-7 activity is enhanced by exogenous heparin, although it is not enhanced by heparan sulfate (38,39). However, in our model, we found that exogenous heparin had no effect on shedding, suggesting that it is unlikely that syndecans are binding to MMPs and directly inhibiting their activity.…”
Section: Discussioncontrasting
confidence: 55%
“…We do not know if the heparan sulfates of syndecan bind to MMPs and inhibit their activity directly. It has been shown in some models that MMP-7 activity is enhanced by exogenous heparin, although it is not enhanced by heparan sulfate (38,39). However, in our model, we found that exogenous heparin had no effect on shedding, suggesting that it is unlikely that syndecans are binding to MMPs and directly inhibiting their activity.…”
Section: Discussioncontrasting
confidence: 55%
“…In the case of LMS, it may be that the expression of versican isoforms with abundant chondroitin sulfate chains (e.g. V0 and V1) by the LMS cells leads to a GAG-dependent localization and activation of cytokines, growth factors, and metalloproteinases (62,63) that promote a proliferative and metastatic microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…substrates, procryptdins (20). Alcian Blue, which is used for detection of sulfated glycosaminoglycans, was reported to stain an outer rim around each granule of Paneth cells (53,67).…”
Section: Discussionmentioning
confidence: 99%